Small and medium-sized enterprise champions promoting climate resilient agriculture in Eastern Africa - Recha, John W.M.; Osumba, Joab J.L.; Byarugaba, Gloria; Wandera, Bright Asiimwe; Oggema, Sebastian; Keizer, Menno; Kasekende, Bashir; Shilomboleni, Helena; Demissie, Teferi Dejene; Radeny, Maren A.O.; Solomon, Dawit (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Sub-Saharan Africa (SSA) is one of the poorest regions in the world, where an estimated 386 million people (48% of the region’s total population) live on less than USD 1.25 per day (Ravallion 2012). This group of people are considered the most vulnerable to climate change as they possess minimum financial and technical resources to cope with climate change (Wheeler and von Braun 2013). In SSA, meteorological disasters, especially droughts and floods, are the most common forms of natural disasters. As such, drought and floods represent 70% of economic losses related to natural hazards in SSA (Bhavnani et al. 2008). Because of climate change, the frequency and intensity of floods and droughts are projected to increase in the future (Bernstein et al. 2008) which negatively affects agriculture.